Analisis Anggaran Biaya dan Waktu Optimal dengan Metode Least Cost Sheduling - Muhammad Ridha; Ulil Mustika Musakkir (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
Cost Scheduling aims to shorten project completion time and look for optimal project schedules using direct, indirect and minimal total costs. This research was conducted on the rehabilitation project of the Lawe alas sub-district office in the Southeast Aceh sub-district. Least. This research was conducted to determine the suitability of physical work in the field with the planning schedule, to find out the optimum amount of time in the project and to know the comparison between the normal costs and costs after the project has accelerated. The calculation results show the normal project implementation time is 182 days with a normal charge of Rp. 160.151.592,33 by adding 1 hour additional working hours hence can speed up time as much as 12 days with additional cost equal to Rp. 2,564,736.09. By adding 2 hours additional hours working hours can accelerate as much as 23 days with an additional cost of Rp. 33.460.241,48. By adding 3 hours additional hours working hours can accelerate as much as 33 days with an additional charge of Rp. 64.355.746,88. By adding 4 hours additional hours working hours can accelerate as much as 42 days with an additional charge of Rp. 95.251.252,27..